1970
DOI: 10.1139/v70-383
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electron scavengers on the γ-radiolysis of gaseous H2S

Abstract: Recent publications ( 1 4 ) have dealt with the effect of electron scavengers on the radiolysis of simple inorganic gaseous hydrides. We would like to present some results of a preliminary study on the radiolysis of gaseous H2S that are, in general, quite different from those above (14).Matheson C.P. grade H,S (99.7 %) was found to contain CO, (-0.2 %) and CS, (< 0.001 %) as impurities when checked by gas chromatography. A 3 m Poropaq Q column maintained at 65 "C, helium carrier gas, and thermal conductivity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…As discussed in the previous section, the fair agreement between the low dose rate yield of G(H,) = 7.0-7.9 (7,9,10) and the limiting yield of G(H,) = 7.9 + 0.3 with SF, at high dose rates suggests that there is no contribution from neutralization at low dose rates. This is confirmed by the absence of an effect of SF, and N 2 0 on G(H2) at low dose rates (1,7,9,10) and it is further confirmed by the limiting yield in multipulse irradiations at high dose rates where G(H,) x 8, and is unaffected by SF,, Figs. 3A and 3B.…”
Section: Low Dose Rate Yieldsmentioning
confidence: 63%
See 3 more Smart Citations
“…As discussed in the previous section, the fair agreement between the low dose rate yield of G(H,) = 7.0-7.9 (7,9,10) and the limiting yield of G(H,) = 7.9 + 0.3 with SF, at high dose rates suggests that there is no contribution from neutralization at low dose rates. This is confirmed by the absence of an effect of SF, and N 2 0 on G(H2) at low dose rates (1,7,9,10) and it is further confirmed by the limiting yield in multipulse irradiations at high dose rates where G(H,) x 8, and is unaffected by SF,, Figs. 3A and 3B.…”
Section: Low Dose Rate Yieldsmentioning
confidence: 63%
“…They also reported that this yield is reduced by the addition of SF,, although they did not state by how much. Huyton and Woodward (7,8) y-irradiated gaseous H2S and measured the dose by ion chamber measurements. They report G(H2) = 7.0 _+ 0.2 at 800 Torr and that neither N 2 0 nor SF, has any effect on this yield (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations